Developing a Nanoparticle-Delivered High-Efficacy Treatment for Infantile Hemangiomas Using a Mouse Hemangioendothelioma Model. Issue 2 (August 2016) - Orbay, Hakan; Li, Yuanpei; Xiao, Wenwu; Cherry, Simon R.; Lam, Kit; Sahar, David E.
Abstract : Background: Current treatments for infantile hemangiomas have unpredictable outcomes. The authors' aim was to develop a nanoporphyrin-delivered, high-efficacy treatment for infantile hemangiomas using a mouse hemangioendothelioma model. Methods: The authors injected mouse hemangioendothelioma cells intradermally to axillary regions of 5-week-old, female, nude mice ( n = 19) to induce hemangioendothelioma growth. They documented nanoporphyrin accumulation in hemangioendotheliomas using positron emission tomography. For the treatment study, the authors randomized hemangioendothelioma-bearing nude mice ( n = 9) into three groups ( n = 3 each). Group I received only saline injections. Group II received only laser treatment after saline injection, and group III received laser treatment after nanoporphyrin injection through the tail vein. The authors followed up the treatment response with digital caliper measurements. Results: Hemangioendotheliomas started to grow approximately 1 week after inoculation and resembled infantile hemangiomas histologically. Nanoporphyrin uptake in hemangioendotheliomas was 19.7 ± 2.2, 16.7 ± 2.02, 8.4 ± 0.3, and 4.9 ± 0.6 percent injected dose per gram of tissue at 3, 6, 24, and 48 hours after injection, respectively. Nanoporphyrin uptake was significantly higher than in blood at 24 and 48 hours after injection ( p < 0.05). Results of ex vivo biodistribution study were consistent with positron emission tomographic imaging. Hemangioendotheliomas in group III started to regress 1 day after the treatment and disappeared totally by day 21. The difference between tumor volumes in group III and other groups was significant on days 17 and 21 ( p < 0.05). Conclusions: Nanoporphyrin accumulated in hemangioendotheliomas at high concentrations, enabling a high-efficacy photodynamic therapy. Given the similarities between hemangioendotheliomas and infantile hemangiomas, this treatment potentially can be a high-efficacy treatment for infantile hemangiomas. Abstract : Supplemental Digital Content is available in the text.